(3efgGL GdgOGjI aj HjGf NeSeGFI BjIs - (3GdHMQGfj, CHh GdfGUQ, GHf GdeJhL, CMeO Hf YHO Gddg Hf eMeO, J (B820 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B...(3gPG hbO jCdfj ef WGYJg ZfjeI hGSYGag HeWdhHg OQLI YGdjI YXjeI Cf CDda dg eNJUQG aj HjGf GdBjGJ GdbQBfjI GdJj YdjgG jOhQ LejY GdCMcGe GdTQYjI hHeYQaJgG (B...s
(3BNQgG (B:s
... (3Ydi QO Mce Gddg JYGdi aj Mce QShd Gddg hGdbGFe ebGeg (B.. {(3hdG JCcdhG CehGdce Hjfce HGdHGWd hJOdhG HgG Edi GdMcGe dJCcdhG aQjbG ef CehGd GdfGS HGdGKe hCfJe JYdehf (B} (3SCd CHh fUQ GdUGOb Ydjg GdSdGe Yf eYfi gPg GdBjI (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\195s
(3GdPQjYI (B23 \ 8558s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs